Linking risk and economic assessments in the analysis of plant pest regulations: the case of U.S. imports of Mexican avocados - Peterson, Everett B.; Orden, David (United States Department of Agriculture, 2006)
This study compares the effects of importing fresh Mexican Hass avocados into the United States under three scenarios for mitigating pest risks. The analysis finds that Scenario 1, adherence to the U.S. phytosanitary rule of November 2004—which removed all seasonal and geographic restrictions on Mexican avocados, while maintaining existing compliance procedures in Mexico—leads to low pest risks for U.S. producers and an estimated annual U.S. welfare gain of $72 million. In Scenario 2, if compliance measures specific to fruit fly control are eliminated along with seasonal and geographic restrictions, pest risks for U.S. producers remain low and there is an additional gain in net U.S. welfare of $1.7 million. Results for Scenario 3, which eliminates all control measures in Mexico, depends on the level of pest-risk estimated. With average risk, there is a gain in net U.S. welfare of about $8.5 million compared with eliminating only seasonal and geographic restrictions, but U.S. producers incur significant pest control costs. With maximum pest-risk estimates, the net gain in U.S. welfare is $16.2 million less than if only geographic and seasonal restrictions are eliminated, with larger pest control costs for U.S. producers and lower consumer welfare gains due to pest-related losses of U.S. avocados.